The Implementation of Learning Cycle 5E to Improve Learning Outcomes of Number Theory of Mathematics Education Study Program Students of Riau University - Syofni, Syofni (Proceedings of the UR International Conference on Educational Sciences, 2018)
This research is a classroom action research that aims to improve the learning process and improve student learning outcomes in Number Theory course. The improvements made were by applying the 5E Learning Cycle learning model. Learning Cycle 5E is based on constructivist learning theory. According to constructivist theory one must build his own knowledge. This 5E Learning Cycle Learning follows 5 stages: 1.Engagement, 2 Exploration, 3.Explanation, 4. Elaboration, 5. Evaluation. This research was conducted in 2 cycles, with sequences of activities, initial reflection, action planning, and implementation of actions, observation and reflection. At the end of each cycle a quiz is carried out, which is useful to observe the development of student learning outcomes from conventional learning to learning by applying the 5E Learning Cycle. The results of observations show improvements in student activities and interactive learning. Analysis of student learning outcomes data also showed an increase in average learning outcomes, namely 57.8 in conventional learning to 64 at the end of cycle 1 by implementing 5E Learning Cycle and becoming 70.8 at the end of the second cycle.